Future Ethical Challenges as Portrayed in Science Fiction Films - Karel Sladek (Communications - Scientific letters of the University of Zilina, 2018)
Fictional worlds of sci-fi films are but visions of the stage humanity (and the world) is coming to given the ever-evolving technological progress. On the one hand, there are optimistic views of scientific development, on the other, there are ethical warnings, especially when a film portrays consequences for humanity and the planet; a vision, in which we crossed the boundaries and fundamentally change the nature of living organisms either by changing their genetic information, or by implanting nanotechnologies. Therefore, the present article reflects on some ethical challenges portrayed in sci-fi films; in particular, we especially concentrate on the meeting point of ethics and religion.